HIERARCHICAL MASS BREAKDOWN FOR TRANSPORT AIRCRAFT WITH TRUSS BRACED WINGS - Murat Taflan; Mert Gulum (MATTER: International Journal of Science and Technology, 2026)
This paper proposes a hierarchical mass breakdown for transport aircraft with truss braced wings. The contribution is not another standalone mass formula, but an integration framework that shows how empirical, semi-empirical, and physics-based mass-estimation methods can be combined without gaps or double counting when an aircraft contains components that are not represented well by conventional handbook mass statements. The need is strongest in novel configurations such as truss braced wing configurations, where the wing box, strut, jury members, and offset often require deeper structural sizing than conventional cantilever wing groups in preliminary design level. The proposed hierarchy maps aircraft mass from takeoff gross weight down to detailed items and, at the same time, visualizes the fidelity level at which each mass method operates. This makes it possible to blend existing aircraft methods with newly developed methods and still roll all results back to operating empty weight and takeoff gross weight in a traceable, accurate way during conceptual and preliminary design phases.